A novel meaningful secret image sharing method based on Arabic letters - Avci, Derya (Academic Publication Council, 2016)
In recent years, to provide information security for multimedia has become an important subject of study. Visual cryptography and secret sharing provide information security without using complex mathematically operators. Thus, visual cryptography and secret sharing are widely used. In this paper, letter based secret image sharing (LSIS) is used for protecting image contents. For this purpose, secret sharing and data hiding algorithms are used together in this LSIS method. The LSIS method consists of two parts. These are generating of meaningful secret sharing and data hiding. Secret sharing and visual cryptography methods commonly generate noise-like images. The noise-like images have attracted the attention of the attackers and several attacks have been developed to break these encrypted images. To prevent these attacks, meaningful secret shares are generated and these secret shares are embedded into cover image. In this paper, a novel secret image sharing method based on Arabic letters is suggested. The proposed method uses Arabic letters for generating meaningful secret shares and data hiding functions are used for camouflage. RGB images are used for cover images. In proposed method, secret shares are embedded into R, G and B channels respectively. Thus, cheatings occurring in visual cryptography are prevented. A secret image sharing method, which is independent morphological features of letters, is obtained by using the proposed method. In this proposed secret image sharing, Arabic letters are used because of Arabic is one of the richest languages in the world. In the data hiding method, 2LSBs data hiding function is used.
Keywords: Data hiding; image processing; information security; meaningful secret image sharing; visual cryptography